Effects of vibration training vs. conventional resistance training among community-dwelling older people with sarcopenia: three-arm randomized controlled trial protocol - Lu, Linqian; He, Xiangfeng; Ma, Lin; Liu, Yu; Chen, Nan (Frontiers in Aging Neuroscience, 2022)
Introduction Sarcopenia is a chronic and progressive disease, which is accompanied by the decline in muscle mass, muscle strength, and physical performance with aging, and it can lead to falls, fracture, and premature death. The prevention and treatment of sarcopenia mainly include exercise therapy and nutritional supplement. Exercise therapy is one of the most potential interventions to prevent and/or delay the progression of sarcopenia. Resistance training (RT), one of the most commonly used exercise types, is widely used in the treatment of sarcopenia, while vibration training (VT) is a prospective strategy for improving sarcopenia in older people. The aim of our study is to compare the effect of VT and RT in older people with sarcopenia on muscle mass, muscle strength, physical performance, blood biomarkers, and quality of life. Methods and analysis Our study is a 12-week, three-arm randomized controlled trial with assessor-blinded. The diagnosis criteria for subject recruitment adopt the guidelines for the Asian Working Group for Sarcopenia. A total of 54 subjects who met the criteria were randomized into one of the following three groups: VT group, RT group, and control group. The VT group and RT group received a 12-week whole-body vibration training and a resistance training program three times every week, respectively. The primary outcome is lower limb muscle strength, and the secondary outcomes include muscle mass, upper limb muscle strength, physical performance, blood biomarkers, and quality of life. We then performed assessments three times, at baseline (0 week), after intervention (12 weeks), and follow-up (24 weeks). The adverse events were also be reported. All outcome measurements were performed by the same researchers. Data were saved in the unified database, and the collected data of all subjects were analyzed by intention-to-treat analysis. Ethics and dissemination This study was reviewed and approved by the Ethical Committee of Xinhua Hospital Chongming Branch. The findings of the study were authorized in peer-reviewed journals with online access; meanwhile, it will be presented at domestic or international academic congresses. Clinical trial registration Chinese Clinical Trial Registry (ChiCTR2100051178), registered on 15 September 2021.